Image thresholding based on two-dimensional histogram oblique segmentation and its fast recurring algorithm - WU Yi-quan; PAN Zhe; WU Wen-yi (Tongxin xuebao)
The obvious wrong segmentation in the existing two-dimensional histogram vertical segmentation method was pointed out. A new two-dimensional histogram oblique segmentation method was proposed,in which the histogram was divided into inner,edge and noise parts by four paralleled oblique lines. The image was thresholded by the oblique line which was perpendicular to the main diagonal. Then the formulae and its fast recurring algorithm of the two-dimensional histogram oblique segmentation method were deduced. Finally,the thresholded images and processing time were given in the experimental result and analysis,which were compared with those of Otsu fast algorithms. The results show that the two-dimensional histogram oblique segmentation could be used in nearly all the two-dimensional histogram thresholding. It makes the inner part uniform,the edge accurate in the thresholded image and has better tolerance capability to noise. At the same time the running time is significantly reduced.